The Influence of Disciplinary Development and Work Motivation on the Performance of Village Midwives at Cireunghas Community Health - Raika Koswara; Dian Lestari (International Journal of Scientific Multidisciplinary Research, 2026)
This study aims to analyze the influence of discipline and work motivation training on the performance of village midwives at the Cireunghas Community Health Center. The uniqueness of this study lies in the measurement of discipline training, which is tailored to the characteristics of village midwives’ duties through the enforcement of regulations, the imposition of sanctions, and ongoing discipline training. The method used in this study was quantitative, employing descriptive and associative approaches. Data were collected via a questionnaire distributed to 33 village midwives and analyzed using multiple linear regression. The results indicate that discipline training, work motivation, and the performance of village midwives fall into the “good” category. This study concludes that consistent improvement in discipline training and strengthening of work motivation can enhance the performance of village midwives. These findings serve as a foundation for Community Health Centers (Puskesmas) in their efforts to improve the quality of health services.